Primary lymphoma arising in Paget’s disease in a patient with primary hyperparathyroidism - Mercedes De La Fuente; Marina Arroyo; Ana S. Collado; Elena C. Gallardo; Santiago Montes; Jose M. Olmos (European Journal of Case Reports in Internal Medicine)
Background: Paget’s disease of bone (PDB) is characterized by a disturbance of the balance between bone formation and bone resorption at one or more bone sites. Its neoplastic transformation to osteosarcoma of the bone has been widely cited in the literature; however, association with non-Hodgkin’s lymphoma (NHL) is very uncommon. In addition, whereas the pathophysiological relationship between PDB and secondary hyperparathyroidism is well established, there is much debate about the association between PDB and primary hyperparathyroidism (PHPT). Case Report: We present a case of NHL arising in pagetoid bone in a 56-year-old man, who was subsequently diagnosed with primary hyperparathyroidism (PHPT). Discussion: The malignant potential of pagetoid bone is well known, with sarcomatous degeneration being the most common neoplasm. Therefore, when pain recurred in our patient, 3 years after treatment of PDB, the presumptive diagnosis was a sarcomatous degeneration of the pagetoid bone. However, bone biopsy revealed a primary lymphoma, an extremely rare association that has been described only in a few cases. In addition, PHPT is rarely associated with PDB, although a link between PHPT and an increased risk of malignancy has been suggested. Conclusion: To the best of our knowledge, this is the first case of these three different bone diseases in the same patient. Further studies are needed to understand the possible molecular basis of the association among these diseases.